Robotic thoracic surgery for neurogenic tumors - Niedermaier, Benedikt Walter; Griffo, Raffaella; Grott, Matthias; Deißner, Henrike; Muley, Thomas; Neumann, Jan-Oliver; Winter, Hauke; Eichhorn, Martin E. (Journal of neurosurgery, 2024)
OBJECTIVE Thoracic neurogenic tumors usually present as benign nerve sheath tumors that can be resected via transthoracic or posterior approaches, depending on the anatomical location. Robot-assisted thoracic surgery (RATS) is increasingly being used for the transthoracic approach, but evidence is very limited. The authors initiated the current study to evaluate the efficacy and safety of RATS for thoracic neurogenic tumors. METHODS This retrospective study is based on a prospectively created database that includes all RATS surgeries between 2018 and 2023. All patients with histologically confirmed neurogenic tumors were included in the study. The patients’ medical and surgical records as well as radiological and pathological findings were analyzed. RESULTS During a 5-year period, 27 patients underwent robotic resection of neurogenic tumors at a high-volume thoracic surgery center. Two patients had previously undergone posterior laminectomy for resection of the intraspinal components. The pathologies included schwannomas (18, 64%), ganglioneuromas (8, 29%), 1 paraganglioma, and 1 neurofibroma occurring close to a schwannoma unilaterally in the same patient. The median tumor size was 4.7 cm (range 0.9-11.4 cm). The median operating time was 69 minutes (range 27-169 minutes), and the median postoperative stay was 3 days (range 1-19 days). There was one conversion due to adhesions after a previous surgery. No major bleeding occurred. There was no perioperative mortality. Morbidity included a lymphatic fistula (n = 1), pneumonia (n = 1), prolonged air leak (n = 1), and 4 cases of postoperative pain persisting for more than 4 weeks. Neurological complications were mostly observed in patients with tumors located at the thoracic apex: 2 cases of Horner’s syndrome, 2 cases with compensatory hyperhidrosis, 1 patient with paresis of the recurrent laryngeal nerve, and a T1 lesion resulting in a minor motor deficit of the small hand muscles (Medical Research Council grade 4) and hypoesthesia of the respective dermatome. CONCLUSIONS RATS for thoracic neurogenic tumors is feasible and safe. Tumors at the thoracic apex are at high risk of neurological deficit and should be approached with care. Close interdisciplinary collaboration between neurosurgeons and thoracic surgeons is necessary for optimal patient selection and a good postoperative outcome.
Online verfügbar: 31. Mai 202
Gesehen am 14.05.2025